2017
DOI: 10.1590/0034-7167-2016-0519
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation of The End-Stage Renal Disease Adherence Questionnaire for hemodialysis patients

Abstract: Objective: To describe the stages in the cultural adaptation of "The End-Stage Renal Disease Adherence Questionnaire" for use in Brazil. Method: A descriptive, transversal study with a quantitative approach. The cultural adaptation followed the steps of translation, professional committee, back translation, panel of patients and pretest. Results: the translation stage created a version in Portuguese that was analyzed by specialists, who suggested alterations in the title, seven sentences in the questions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Wondering when they were happy with their sex life, most reported the following: Yes I am happy. ( Interviewee 1,4,5,7,8,14,20,22,23,24,25,27,32,38,) It is said that when asked about what he used to minimize or try to solve his problems about sexuality, most reported that he does nothing; others reported the use of drugs.…”
Section: In the Beginning I Had Depression So I Traveled A Lot And mentioning
confidence: 99%
See 2 more Smart Citations
“…Wondering when they were happy with their sex life, most reported the following: Yes I am happy. ( Interviewee 1,4,5,7,8,14,20,22,23,24,25,27,32,38,) It is said that when asked about what he used to minimize or try to solve his problems about sexuality, most reported that he does nothing; others reported the use of drugs.…”
Section: In the Beginning I Had Depression So I Traveled A Lot And mentioning
confidence: 99%
“…Anything. ( Interviewees 1,3,5,7,8,14,20,21,22,23,24,25,27,32,38,39) The little blue. ( Interviewees 26,33) The following accounts were alleged by other subjects.…”
Section: In the Beginning I Had Depression So I Traveled A Lot And mentioning
confidence: 99%
See 1 more Smart Citation
“…CKD requires changes in daily habits that influence the patient's quality of life. The patient's pro-activity in facing the new condition is paramount (3) , considering its social, physical, psychological, and emotional nature, as well as its implications over habits, sex life, independence, and autonomy.…”
Section: Introductionmentioning
confidence: 99%